Efektivitas Sistem Informasi Akuntansi, Kemampuan Teknis Pengguna, dan Penggunaan Teknologi Informasi pada Kinerja Karyawan - Listiani, Ni Kadek; Yadnyana, I Ketut (E-Jurnal Akuntansi; Vol 34 No 2 (2024), 2024)
The aim of this research is to empirically prove the influence of the effectiveness of accounting information systems, user's technical abilities and the use of information technology on employee performance. This research was conducted at 16 KSU units in Susut District. The population in this study was 74 people, with the sample determination method using purposive sampling so that a sample of 52 samples was obtained. Data collection was carried out using interview methods, questionnaires with a 5-point Likert Scale, and observation using data analysis techniques, namely multiple linear regression analysis with the help of SPSS version 25 software. The results of this research show that the effectiveness of the accounting information system, the user's technical abilities and the use of information technology have an influence positive and significant on employee performance. Keywords: AIS Effectiveness; User’s Technical Ability; IT Use; Employee Performance